Pengembangan Modul Praktikum Osiloskop Untuk Meningkatkan Pemahaman Konsep Arus Bolak-Balik Mahasiswa Politeknik Negeri Bandung - I Gede Rasagama (Department of Physics Education, Universitas Mataram, 2019)
The usefulness of the concept of alternating current is very functional for polytechnic students because it provides a basic theory of the production and use of electrical energy. At the Bandung Polytechnic Physics Laboratory, the oscilloscope practicum does not seem to have comprehensively verified the concept of alternating current. Understanding the concept of alternating current has become an urgent need and an indicator of the success of the learning process of Physics for graduates of DIII and DIV of several Bandung State Polytechnic study programs. The main objective of the research is to produce an oscilloscope practicum module that is able to support the learning of the concept of alternating current for Bandung State Polytechnic students through the optimization of the functions of existing equipment and the procurement of new equipment. Through the R & D approach (preliminary study, the design phase, development stage, and validation stage) have produced 2 digital oscilloscope practicum modules, which are assisted by Hantek-DSO-2090. The test results show: the two modules are able to verify the concept of alternating current; practicum with modules has a significant effect on increasing understanding of the concept of alternating current students; practicum module received positive responses from almost all students; and working on practicum modules is felt easy by students even though the material is considered difficult.